Anthroponyms in the onomastic space kumyk folklore tales - Ruganiyat A. Musayeva (Кавказология, 2025)
The topic focuses on anthroponyms used in folklore texts.  The work's goal is to investigate human names in Kumyk folk story texts, identifying their semantic aspects, frequency of usage, and role and function as linguistic methods that contribute to the development of creative pictures.  The research examines the composition and organization of the anthroponymic realm, revealing the characteristics of how the Kumyk onyms function.The research revealed that anthroponyms in folklore tales play a crucial role in narrative formation.  They provide a pretty comprehensive picture of Kumyk onomastics as a whole, with traits indicating relationship with other Turkic languages.Linguists who specialize in folklore onomastics will be particularly interested in this article.  It is also relevant to a wide spectrum of philologists, as the author focuses on the nature of the interaction of linguistic and non-linguistic information in the content of proper names.